Editorial [Hot Topic:Applications of Angiotensin Converting Enzyme Inhibitors and of Angiotensin II Receptor Blockers in Pharmacology and Therapy: An Update (Executive Editor: Agostino Molteni)] - Molteni, Agostino (Current Pharmaceutical Design, 2007)
About three years ago we discussed in this Journal the development of additional potential applications of angiotensin converting enzyme inhibitors and of Angiotensin II (ANG II) receptor blockers in therapy. The deployment of these drugs in the treatment of diverse vascular conditions has been, for many years, a well established medical practice and every year millions of individuals benefit from this treatment. This successful deployment underlines the relevance that the reninangiotensin- aldosterone system (RAAS) plays in the regulation of the control mechanisms of our blood pressure and, more in general, of our homeostasis. It emerged, however, from many articles of that publication that the RAAS system and ANG II in particular, play additional roles in the modulation of our homeostasis such as the regulation of apoptosis, the modulation of cellular growth, specifically of fibroblasts and endothelial cells, and the modulation of angiogenesis. Additional information has been added in the past two-three years to these data. More knowledge also became available about the RAAS system genetic regulation, its interaction with prostaglandins and with other substances also controlling blood pressure, and about the presence and physiological role of another converting enzyme: ACE II. The presence of the various components of the system at local level in several tissues has also become relevant, especially their action on the smooth muscle fibers of the wall of arteries and arterioles of several organs, kidneys, and lungs in particular, or for the apoptotic regulation of many tissues. All these observations open the possibility of the deployment of ACE inhibitors and of A2 receptors antagonists as pharmacological modulators of many diseases other than hypertension. This journal's issue reviews and revises some of the previous experiences with these drugs and deals with some novel applications and deployments of them. Drs. Hamdi and Castellon [1] discuss the role that ACE polymorphism plays with a large number of diseases including cardiovascular, metabolic, immune, cancer, aging, neurodegenerative and psychiatric disorders and they report and summarize these associations. These observations lead to the question why this ACE polylmorphism is associated with so many diseases and what its function is. In the past, much attention has been given to the role that ACE, especially somatic ACE, plays on the synthesis of Angiotensin II in different tissues and on the extensive role that this octapeptide plays in the general homeostasis regulation. ACE, however, has been found to convert many other peptides and the investigation of these functions is extended to test the association of this polymorphism with the levels of other ACE isoenzymes. The experience with various ACE isoforms and their effect on cell's survival may better explain the ACE/ID polymorphism associated with many diseases. Drs. Igic and Behnia [2] report the pharmacological, immunological and genetic targeting of the Renin-Angiotensin system for the treatment of cardiovascular diseases. The investigators present the various components of the Renin Angiotensin system (RAS), discuss the biological activities of angiotensin peptides and the role of the enzymes that generate and metabolize the various types of angiotensin. They devote special attention to the role of Renin, ACE, ACE 2, chymase and neprylysin. Subsequently, on the basis of the experience with ACE inhibitors and type 1 ANG II receptor blockers, they discuss the rationale to target the RAS in its control of general homeostasis. Finally, they present the investigational agents acting on the RAS, which posses a potential for clinical deployment and give the perspective of pharmacological immunological and genetic targeting of the RAS for the treatment of cardiovascular diseases. Dr. Heffelfinger [3] discusses the role of RAS in the regulation of angiogenesis. It is well established that ANGII and bradykinin are angiogenic agents and affect the microvascular circulation. That implies that the ACE inhibition would have an impact on angiogenesis in vivo depending upon which factors are present in the system. The author reviews several conditions such as peripheral ischemia, stroke, retinopathy and cancer in relation to ANGII and bradykinin activity and evaluates the impact that ACE inhibitors posses in all those clinical conditions. It appears that peripheral ischemia and stroke seem to be dependent for angiogenesis regulation by bradykinin signaling, while cancer and retinopathy are more dependent upon ANGII. Published data on in vitro cultures as well in animal models suggest interesting predictions about how the RAS and bradykinin may function in humans and many data are now accumulating in humans confirming the data derived from experimental work. Modulation of angiogenesis by ACE inhibitors and ANG II receptor blockers may become a new therapeutical property of these drugs.........